Metabolomics - New Insights Into Biology and Medicine 2020
DOI: 10.5772/intechopen.88924
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicines for Cancer Treatment from the Metabolomics Perspective

Abstract: Cancer is one of the most prevalent diseases all over the world with poor prognosis and the development of novel therapeutic strategies is still urgently needed. The large amount of successful experiences in fighting against cancer-like diseases with Chinese medicine has suggested it as a great source of alternative treatments to human cancers. Cancer cells have been shown to own a predominantly unique metabolic phenotype to facilitate their rapid proliferation. Metabolic reprogramming is a remarkable hallmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The inhibitory activities of the two extracts on lipid peroxidation were comparable [107]. Extracts of C. zedoaria had a moderate antimutagenic effect against mutation induced by benzo [a] pyrene [9][10][11].…”
Section: Curcuma Zedoariamentioning
confidence: 91%
See 1 more Smart Citation
“…The inhibitory activities of the two extracts on lipid peroxidation were comparable [107]. Extracts of C. zedoaria had a moderate antimutagenic effect against mutation induced by benzo [a] pyrene [9][10][11].…”
Section: Curcuma Zedoariamentioning
confidence: 91%
“…Anti-mutagenic activities of extracts of various medicinal plants have been evaluated by using the microsomal system/Salmonella to investigate whether they contain direct or indirect anti-mutagens. Many plant extracts show anti-mutagenic activity, including Pteris multifida, Smilax china and Prunella vulgaris [9][10][11]. For example, Sukumaran et al [12] reported the inhibition of tobacco-induced mutagenesis by eugenol and plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…B-5354c, which is produced by a marine bacterium, inhibits SPHK1 and SPHK2 with similar efficiencies ( 131 ) and acts on sphingosine in a noncompetitive manner. B-5354c can reduce the size of PC-3 tumors in vivo when combined with the chemotherapy drug irinotecan and can sensitize PC-3 and LNCaP prostate cancer cells to chemotherapy drugs, such as docetaxel and camptothecin ( 132 ). B-5354c has been further demonstrated to act as a chemosensitizer of PC-3 cells when used in conjunction with docetaxel ( 133 ).…”
Section: Natural Products For Sphingolipid-based Anticancer Therapeuticsmentioning
confidence: 99%
“…Network pharmacology is to explore the mechanism of TCM in the treatment of HCC by integrating bioinformatics and molecular docking technology. Previous studies revealed that many decoctions may play an anti-HCC role by regulating specific signaling pathways and biological processes [18], which provides a new idea for the treatment of HCC, making traditional Chinese medicine play an important role in anti-cancer research. However, further research is still needed in this field to further understand the potential mechanism of TCM in the treatment of HCC and lay the foundation for individualized treatment and more effective clinical application.…”
Section: Introductionmentioning
confidence: 99%